Pre-service Teachers' Beliefs About Inclusive Education Before and After Multi-Compared to Mono-professional Co-teaching: An Exploratory Study - Ritter, Roswitha; Wehner, Antje; Lohaus, Gertrud; Krämer, Philipp (Frontiers in Education, 2019)
Teacher beliefs are action guiding in the classrooms. Teacher beliefs about inclusive education are thus a crucial pre-requisite for its success. Therefore, those beliefs have to be addressed during the first phase of teacher training. Generally accepted concepts or operationalized definitions would be valuable guidelines for pre-service teachers and their educators. However, neither the ones nor the others are available at present. Therefore, pre-service teachers have to fall back on their own beliefs, a rather unexplored notion so far. Within the present study, pre-service teachers’ beliefs about inclusive education were assessed before and after an academic seminar. During this academic seminar, participants co-taught in either multi-professional (i.e. one pre-service teacher for special educational needs and one for general education) or mono-professional (i.e. both pre-service teachers for special educational needs or both for general education) teams in inclusive classes of secondary schools. Pre-service teachers’ beliefs were assessed with the help of concept-maps, which were created by the participants at two testing times. The concept-maps were analyzed employing graph-theoretical approaches as well as qualitative, summarizing content analysis methods. Results show that pre-service teachers who worked in multi-professional teams expanded their conceptualization of inclusive education to include facets like individualization and differentiation, while pre-service teachers who worked in mono-professional teams displayed no such expansion. Also, the conceptualization of pre-service teachers who worked in mono-professional teams contained a larger percentage of propositions addressing disadvantages and negative consequences of inclusive education. Therefore, it is concluded that multi-professional co-teaching during teacher training helps prepare teachers for successful inclusive education.